Rural sustainability and food choice: The effect of territorial characteristics on the consumers' preferences for organic lentils - Chiara Paffarini; Bianca Maria Torquati; Tiziano Tempesta; Sonia Venanzi; Daniel Vecchiato (Agricultural and Food Economics, 2021)
The importance of pulse cultivation and consumption is recognized by the scientific community in terms of human nutrition, food security, biodiversity and a valid substitute for animal protein. In some marginal areas, pulse cultivation represents also a protection against the abandonment of agricultural land, the preservation of traditional landscape and the maintenance of natural environments, besides contributing to the safeguard of traditional gastronomy and culture.
Keywords: 330; Attribute non-attendance; Choice experiment; Natura 2000 SCIs; PDO; PGI; Traditional rural landscape